Landscape Illustration Flashing in Al-Aghouati Trip - GASMI, CHahinaz; Bensari, MESSAOUD (Milev Journal of Research and Studies, 2022)
Travel literature used to be a favorite resource for intelligentsia in general ; historians depend on it as an authentic document and ;geographers explore more about the countries and places ;anthropologists try to study the origin and development of human societies; cultures ;customs ; and tradition . As for the writer; he will be involved in different literary styles ,storytelling fact and fiction ; narration ;description ;dialogue and exciting scenes. This article aims to shed light on the Ibn E-Din Al- Aghouati travel document which was dominated by a brief flash description ; without prejudice to the meaning.